Validation of a novel multivariate method of defining HIV-associated cognitive impairment - Underwood,J; de,francesco D; Cole,JH; Caan,MWA; Van,Zoest RA; Schmand,BA; Sharp,D; Sabin,CA; Reiss,P; Winston,A (Open Forum Infectious Diseases, 2019)
BackgroundThe optimum method of defining cognitive impairment in virally suppressed people-living-with-HIV is unknown. We evaluated the relationships between cognitive impairment, including using a novel multivariate method (NMM), patient reported outcome measures (PROMs) and neuroimaging markers of brain structure across three cohorts.MethodsDifferences in the prevalence of cognitive impairment, PROMs and neuroimaging data from the COBRA, CHARTER and POPPY cohorts (total n=908) were determined between HIV-positive participants with and without cognitive impairment defined using the HIV-associated neurocognitive disorders (HAND), global deficit score (GDS) and NMM criteria.ResultsThe prevalence of cognitive impairment varied by up to 27% between methods used to define impairment (e.g. 48% for HAND vs. 21% for NMM in the CHARTER study). Associations between objective cognitive impairment and subjective cognitive complaints were generally weak. Physical and mental health summary scores (SF-36) were lowest for NMM-defined impairment (p’s<0.05).There were no differences in brain volumes or cortical thickness between participants with and without cognitive impairment defined using the HAND and GDS measures. In contrast, those identified with cognitive impairment by the NMM had reduced mean cortical thickness in both hemispheres (p’s<0.05), as well as smaller brain volumes (p<0.01). The associations with measures of white matter microstructure and brain-predicted age were generally weaker.ConclusionDifferent methods of defining cognitive impairment identify different people with varying symptomatology and measures of brain injury. Overall, NMM-defined impairment was associated with most neuroimaging abnormalities and poorer self-reported health status. This may be due to the statistical advantage of using a multivariate approach.